Electrochemiluminescent sensors as a screening strategy for psychoactive substances within biological matrices. Issue 12 (5th June 2020) - Brown, Kelly; Jacquet, Charlotte; Biscay, Julien; Allan, Pamela; Dennany, Lynn
Abstract : Electrochemiluminescent sensors for point-of-care devices; a screening strategy for the direct detection of hallucinogens within a variety of biological matrices. Abstract : With the rapid growth and appearance of novel psychoactive substances (NPS) onto the global drug market, the need for alternative screening methodologies for implementation within clinical environments is substantial. The immunoassay methods currently in use are inadequate for this new drug trend with the potential for misdiagnosis and subsequent administration of incorrect patient treatment increased. This contribution illustrates a strong proof-of-concept for the use of electrochemiluminescence (ECL) as a screening methodology for NPS within biological fluids, using the hallucinogen scopolamine as a model compound. A low cost, easy-to-use and portable sensor has been developed and successfully employed for the detection of scopolamine at clinically relevant concentrations within a variety of biological matrices, including human pooled serum, urine, artificial saliva and sweat, without any prior sample preparation required. Moreover, assessment of the sensor's potential as a point-of-care wearable device was performed with sample collection from the surface of skin, demonstrating its capability for the qualitative identification of scopolamine despite collection of only minimal volumes off the skins surface. The developed sensor described herein exhibits a strong proof-of-concept for the employment of such ECL sensors as point-of-care devices, where the sensors ease of use and removal of time-consuming and complex sample preparation methods will ultimately increase its usability by physicians, widening the avenues where ECL sensors could be employed.